N-aldehyde-modified phosphatidylethanolamines generated by lipid peroxidation are robust substrates of N-acyl phosphatidylethanolamine phospholipase D - Reza Fadaei; Annie C. Bernstein; Andrew N. Jenkins; Allison G. Pickens; Jonah E. Zarrow; Abdul-Musawwir Alli-Oluwafuyi; Keri A. Tallman; Sean S. Davies (Journal of Lipid Research, 2025)
N-acyl phosphatidylethanolamine-hydrolyzing phospholipase D (NAPE-PLD) hydrolyzes phosphatidylethanolamines (PEs) where the headgroup nitrogen has been enzymatically modified with acyl chains of four carbons or longer (N-acyl-PEs or NAPEs). The nitrogen headgroup of PE can also be nonenzymatically modified by reactive lipid aldehydes, thus forming N-aldehyde-modified PEs (NALPEs). Some NALPEs such as N-carboxyacyl-PEs are linked to PE via amide bonds similar to NAPEs, but others are linked by imine, pyrrole, or lactam moieties. Whether NAPE-PLD can hydrolyze NALPEs was unknown. We therefore characterized the major NALPE species formed during lipid peroxidation of arachidonic acid and linoleic acid and generated various NALPEs for characterization of their sensitivity to NAPE-PLD hydrolysis by reacting synthesized aldehydes with PE. We found that NAPE-PLD could act on NALPEs of various lengths and linkage types including those derived from PE modified by N-malondialdehyde, N-4-hydroxynonenal, N-4-oxo-nonenal, N-9-keto-12-oxo-dodecenoic acid, and N-15-E2-isolevuglandin. To assess the relative preference of NAPE-PLD for various NALPEs versus its canonical NAPE substrates, we generated a substrate mixture containing roughly equimolar concentrations of seven NALPEs as well as two NAPEs (N-palmitoyl-PE and N-linoleoyl-PE) and measured their rate of hydrolysis. Several NALPE species, including the N-4-hydroxynonenal-PE pyrrole species, were hydrolyzed at a similar rate as N-linoleoyl-PE, and many of the other NALPEs showed intermediate rates of hydrolysis. These results significantly expand the substrate repertoire of NAPE-PLD and suggest that it may play an important role in clearing products of lipid peroxidation in addition to its established role in the biosynthesis of N-acyl-ethanolamines.